Nanoparticle shapes effects on MHD flow of hybrid nanofluid over a stretching/shrinking sheet with slip and chemical reaction - Yahaya, Rusya Iryanti; Md Arifin, Norihan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Scientific.Net, 2022)
The impact of nanoparticle shapes (i.e., blade, brick, cylindrical, platelet, and spherical) on the MHD flow of Ag-MgO/water hybrid nanofluid over a stretching/shrinking sheet is scrutinized in this study. Chemical reaction and activation energy are included in the governing partial differential equations of the flow problem. On the boundary, velocity slip and zero mass flux conditions are considered. The simplification of the governing equations and boundary conditions into non-linear ordinary differential equations is done through similarity transformation. Then, the bvp4c solver in Matlab is deployed for computation, with the results generated in the form of numerical solutions and graphs. It is found that the usage of spherical-shaped nanoparticles produces the lowest magnitude of skin friction coefficient, and the implementation of blade-shaped nanoparticles in the hybrid nanofluid provides the highest enhancement of heat transfer rate. The increment in activation energy slows down the chemical reaction that raises the concentration profile of the hybrid nanofluid. However, the concentration profile decreases as the reaction rate increases.